Comprehensive Metabolomic Profiling in Adults with X-Linked Hypophosphatemia: A Case-Control Study - López-Romero, Luis Carlos; Broseta, José Jesús; Roca-Marugán, Marta; Máñez Ramírez, Noemí; Hernández-Jaras, Julio (Biomedicines, 2025)
Background: X-linked hypophosphatemia (XLH) is a rare disorder characterized by elevated levels of fibroblast growth factor 23 (FGF-23), leading to hypophosphatemia and complications in diagnosis due to its clinical heterogeneity. Metabolomic analysis, which examines metabolites as the final products of cellular processes, is a powerful tool for identifying in vivo biochemical changes, serving as biomarkers of pathological abnormalities, and revealing previously uncharted metabolic pathways. Methods: A multicenter cross-sectional case-control study of adult patients diagnosed with XLH was conducted. Serum metabolomic analysis was performed with an Ultra-Performance Liquid Chromatography equipment (UPLC) coupled to a high-resolution mass spectrometer (MS). An analysis of metabolic pathways using MetaboAnalyst version 5.0 and a quantitative enrichment analysis (QEA) was performed. We employed multivariate statistical models, including a principal component analysis (PCA) and an orthogonal partial least squares discriminant analysis (OPLS-DA) regression model. Results: A cohort of 20 XLH patients and 19 control subjects were recruited. A total of 104 metabolites were identified. The differential metabolites identified included glycine, taurine, hypotaurine, phosphoethanolamine, pyruvate, guanidoacetic acid, serine, succinate, 2-aminobutyric acid, glutamine, 2-hydroxyvaleric acid, methionine, ornithine, phosphorylcholine, hypoxanthine, lysine, and N-methylnicotinamide. Enrichment analysis identified disturbances in key metabolic pathways, including phosphatidylethanolamine biosynthesis, sphingolipid metabolism, and phosphatidylcholine biosynthesis. Additionally, pathways related to cysteine metabolism, glycolysis, and pyruvate metabolism. Conclusions: This study identified significant differences in the metabolic profiles of individuals with XLH compared to healthy controls. These findings enhance understanding of potential pathogenic mechanisms and offer a metabolic basis for further in-depth investigations into XLH.